PENGARUH VARIASI MENU DAN HARGA TERHADAP LOYALITAS PELANGGAN GEN’Z MIE GACOAN DI SIDOARJO DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL MEDIASI - Briliantine Caesar Eka Wantoro; Ayu Lucy Larassaty; Achmad Zaki; Afifatus Sholikhah (POLITEKNIK LP3I JAKARTA, 2025)
This study uses purchasing decisions as a mediator to test how price and menu variety affect Generation Z loyalty at Mie Gacoan Sidoarjo. Quantitative methods and explanatory analysis were used to collect data from 170 respondents through questionnaires. PLS-SEM analysis revealed that although menu changes have a large impact on the decision to purchase, they do not directly increase consumer loyalty. Meanwhile, price has a great influence on loyalty and purchase decisions. The results of this study emphasize how important menu innovation and aggressive pricing tactics are to increase consumer loyalty through wise purchases.